Abordagem de controle para a operação descarregada de grandes plantas fotovoltaicas sob condições de sombreamento parcial causado por nuvens - Dilger, Eric Bernard (2023)
The increased participation of stochastic energy sources complicates the operation and planning of modern electrical power systems. As a result, some network codes already request the involvement of large-scale photovoltaic generation in ancillary services to support the electrical grid. The conventionally adopted solution consists of including battery systems next to the generation plant. However, this alternative increases the cost and complexity of photovoltaic plants, which has led to the proposition of new, more sophisticated control methods without additional equipment. This work proposes a control approach for operation with power reserve in large photovoltaic plants composed of dozens of inverters operating in parallel. The strategy's objective is to establish an active power reserve in the operation of the photovoltaic plant to provide ancillary services of frequency regulation considering typical shading scenarios imposed by clouds. A compensation technique is proposed to mitigate de power fluctuation inherent estimative strategies based on P-V curve scan and disturb de grid. Additionally, a methodology based on fractal geometry is proposed to emulate the typical movement of clouds over PV plants, which allows the synthesis of realistic irradiance variations and the consideration of multiple climatic and technical parameters in the mathematical model adopted to represent a 100 MWac photovoltaic plant in an ambient environment. of computer simulation. An analysis of the independent impact of these parameters on the variability of generated power was obtained by studying multiple scenarios with different levels of cloud cover. The proposed compensation technique enabled power reserve control of the photovoltaic plant with a maximum deviation of 1.79% for the most critical shading scenario. The approach allows intending power reserves to track supplementary active power signals with ramp rates greater than 19 MW/min. A droop regulator was evaluated for the photovoltaic plant operation in parallel with a synchronous generator and resulted in a 60% reduction of the maximum frequency sag. This study also uses the photovoltaic array in non-homogeneous irradiance conditions to evaluate the impact of partial shading in a group composed of thousands of modules. It shows that the effect of multiple peaks is smoothed by increasing strings associated in parallel.